The Influence of Capital Intensity and Foreign Ownership on Tax Avoidance in Consumer Goods Industry Companies - Dalimunte, Devi Sarmila; Fitri, Euis Nessia (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the effect of capital intensity and foreign ownership on tax avoidance in consumer goods sector companies listed on the Indonesia Stock Exchange. Using a quantitative approach with associative research design, the data were analyzed through multiple linear regression. The population in this study includes all consumer goods manufacturing companies listed during the period of observation, while the sample consists of selected companies in the food and beverage subsector that meet specific criteria using purposive sampling. The research findings indicate that both capital intensity and foreign ownership have significant positive influences on corporate tax avoidance. Companies with substantial capital investment and higher proportions of foreign ownership tend to engage more actively in tax avoidance strategies. These results highlight the role of ownership structure and asset composition in shaping corporate tax behavior. The study contributes to the existing literature and offers insights for policymakers to strengthen tax regulation and improve compliance.